Bridging Faith and Critical Inquiry: Implementing Resource-Based Learning to Enhance Critical Thinking in Pesantren English Education - Saputra, Heru (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This study investigates the integration of Resource-Based Learning (RBL) in English education within an Islamic boarding school (pesantren) to enhance students’ critical thinking while maintaining faith-based educational values. Employing a mixed-methods design, the research combined quantitative and qualitative data to capture both measurable learning outcomes and pedagogical dynamics. The participants were twenty-seven male santri of Ma’had Al-Jamiah UIN Salatiga who engaged in RBL-based English instruction over one semester. Quantitative data were obtained through pretest–posttest comparisons, while qualitative insights were drawn from interviews, focus group discussions, and classroom observations. The results revealed a significant improvement in students’ critical thinking performance (t = 12.68, p .05; Cohen’s d = 1.9), confirming the effectiveness of RBL in fostering analytical reasoning. Qualitative findings indicated that RBL promoted faith-based autonomy, reflective dialogue, and transformative engagement, allowing santri to connect inquiry with moral reflection. The integration of Islamic values into RBL created a learner-centered environment that harmonized intellectual growth with spiritual awareness. The study concludes that RBL is a viable and culturally responsive model for English education in pesantren, bridging the gap between faith and critical inquiry while encouraging teachers to adopt facilitative, resource-oriented pedagogies. Future research is encouraged to explore long-term and multi-institutional applications of RBL to strengthen its role in developing ethically grounded, globally competent learners.